2015
DOI: 10.1037/spy0000025
|View full text |Cite
|
Sign up to set email alerts
|

Parent goals and verbal sideline behavior in organized youth sport.

Abstract: The present study examined the alignment of goals parents construct for their children with parent verbal sideline behavior at the earliest stage of youth sport. Semistructured interviews, parent journals, and in situ observation were employed with 4 parents over the initial 15 months of their children’s organized sport participation. Parent goals were categorized within the multiple goals framework (Caughlin, 2010; O’Keefe & Shepherd, 1987), verbal sideline behaviors were categorized using Holt, Tamminen, Bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 30 publications
5
81
0
Order By: Relevance
“…Dorsch and colleagues [11] used a mixed-methods approach with many sources of qualitative data and quantitative observational data. We sought to expand the research base by quantitatively documenting parent cardiovascular and metabolic parameters in and around their son's competition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dorsch and colleagues [11] used a mixed-methods approach with many sources of qualitative data and quantitative observational data. We sought to expand the research base by quantitatively documenting parent cardiovascular and metabolic parameters in and around their son's competition.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in youth sport, the spectators relate to the youth participants -namely parents. Researchers have reported that parents serve a vital role in athlete development [7], a source of youth enjoyment [8][9][10], and express a broad range of verbal reactions during sporting contests [11][12]. Given the importance of parents to the youth sports experience, it is surprising that researchers have not examined the physiological responses and thus demands of spectating their children.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Explanatory and descriptive studies, while illuminating several important facets of parent-child interaction in sport, have failed to offer theoretical explanations for their findings (see, Bloom & Drane, 2008;Bowker, Boekhoven, Nolan, Bauhaus, Glover, Powell, & Taylor, 2009;Hennessey & Schwartz 2007;Omli & LaVoi, 2006). Very few researchers have applied a lens informed by family, human development, and interpersonal communication theory (c.f., Dorsch, Smith, Wilson, & McDonough, 2015a;Dorsch, Smith, & McDonough, 2015b;Holt et al, 2008). These frameworks, when taken in light of the significant contributions made by more "traditional" sport psychology theories, have the potential to greatly enhance scholars' understanding of communication among family members surrounding the context of sport (Holt et al, 2008).…”
mentioning
confidence: 99%
“…In contrast, Holt and colleagues (2008) categorized parent verbal reactions on a continuum from supportive to controlling (praise/encouragement, performance contingent feedback, instruction, striking a balance, negative comments, and derogatory comments) when exploring the verbal reactions of four families in sport (Holt, Tamminen, Black, Sehn, & Wall, 2008). This framework has also recently been applied to the examination of links between parent verbal sideline behaviours and goals for their children's sport participation (Dorsch, Smith, Wilson, & McDonough, 2015). Overall, these studies have reported an assortment of parent sport communications considered both detrimental and supportive to children's development.…”
Section: Analyses Of Parent Verbal Commentsmentioning
confidence: 99%